FEATURES OF PRIMARY RESISTANCE OF MYCOBACTERIUM TUBERCULOSIS TO RIFAMPICINUM IN PATIENTS WITH NEWLY DIAGNOSED TUBERCULOSIS - Островський, М. М.; Баблюк, Л. А.; Макойда, І. Я.; Мельник, О. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Due to the prevalence of resistant of Mycobacterium, described features of the epidemiological situation in patients with newly diagnosed pulmonary tuberculosis, which are treated in the bacteria discharging department of Regional Clinical Pulmonology Center. At performed molecular genetic screening test Gpert MBT / RIF, positive result was in 13.0% of patients. When conducted cultural research by BACTEC ™ MGIT ™ 960 DST test, multi-resistant TB was in 10.4% of patients and advanced resistance of tuberculosis – 2.0%.